KONTRIBUSI CITRA MEREK SEBAGAI VARIABEL MEDIASI PADA INFLUENCER MARKETING DAN VIRAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK (Pada Aplikasi Tiktok Di Kalangan Gen Z) - novel reonald; Dian Irma Aprianti; Reva Saila Mutia (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2026)
The widespread use of TikTok as a digital entertainment and commerce platform has prompted the need to explore the determinants of Generation Z consumer behavior. This study examines the influence of social media marketing strategies, influencer marketing, and brand image on the purchasing decision-making process through TikTok Shop. An explanatory quantitative method was used, involving 130 Generation Z respondents (18-26 years old) in Samarinda who had experience shopping on TikTok. Data analysis was conducted using multiple linear regression techniques supported by Warppls software. The results show that influencer marketing has a positive and significant effect on brand image, viral marketing has a positive and significant effect on brand image, influencer marketing has a positive and significant effect on repurchase decisions, and viral marketing has a positive and significant effect on repurchase decisions. This study also found a positive and significant effect between brand image as a mediator between influencer marketing and viral marketing on purchasing decisions.